A New Public Health Risk: Information Overload and the Harmful Effects of Information Technology on Cognitive Health - Pascoal, R.; Joaquim Paulo Moreira (Public Health Risks: Detection, Management and Control, 2026)
This research examines the impact of information overload as a detrimental factor to cognitive health. In addition to human limitations in understanding due to information overload, limitations are also often related to limited capacities, especially when real-time information requires additional tasks while performing other tasks simultaneously. In this context, it is relevant to understand the degradation of attention when working with information technologies when attention is required to other information. Through eight computer experiments, the response times and memory of volunteers were evaluated. A comparative analysis was made between a test without overload and a test with information overload, and the volunteers showed degradation in their response times as well as in their memory retention capacity.